Time's up! : dating the Minoan eruption of Santorini : acts of the Minoan eruption chronology workshop, Sandbjerg November 2007, initiated by Jan Heinemeier & Walter L. Friedrich (Monographs of the Danish Institute at Athens 1397-1433, 2010)
Editor's preface /David A. Warburton --General introduction /David A. Warburton --The Minoan eruption of Santorini radiocarbon dated to 1613 ± 13 BC /Walter L. Friedrich & Jan Heinemeier --Evidence, geology, archaeology & chronology.Volcanic chronology of Santorini /Alexander R. McBirney ;The eruption within the debate about the date /Floyd W. McCoy ;The effects of the Minoan eruption /Walter L. Friedrich & Nikolaos Sigalas ;Evidence from Pseira for the Santorini eruption /Philip P. Betancourt ;The impact of the Minoan eruption of Santorini on Mochlos /Jeffrey S. Soles ;Papadiokambos :new evidence for the impact of the Theran eruption /Thomas M. Brogan & Chrysa Sofianou ;The basis for the Egyptian dates /Rolf Krauss & David A. Warburton ;How uncertain is Mesopotamian chronology? /Hermann Hunger --Debate :typology, chronology, methodology.Thera, Hatshepsut, and the Keftiu :crisis and response /J. Alexander MacGillivray ;The Thera eruption and Egypt :pumice, texts and chronology /Karen Polinger Foster, Johannes H. Sterba, Georg Steinhauser & Max Bichler ;The date of the Late Bronze Age eruption of Santorini /Peter Warren ;Aegean-Egyptian synchronisms and radiocarbon chronology /Felix Höflmayer ;The state of the debate aaboutthe date of the Theran eruption /Malcolm H. Wiener ;Beyond the Santorini eruption /Sturt W. Manning ;The dating of the earlier Late Minoan IA period /Sturt W. Manning & Christopher Bronk Ramsey ;Chronological conundrums :Cypriot and Levantine imports from Thera /Robert Merrillees ;The chronology of Tell el-ʻAjul, Gaza /Peter M. Fischer ;An update on the chronological value of Minoica in the Levant and Cyprus /Annette Højen Sørenson ;¹⁴C and ¹⁰Be around 1650 cal BC /Raimund Muscheler ;The Minoan eruption of Santorini radiocarbon dated /Jan Heinemeier, Walter L. Friedrich, Bernd Kromer & Christopher Bronk Ramsey --Epilogue /David A. Warburton.